Current Clinical Perspectives on Takotsubo Syndrome: Comprehensive analysis of Diagnosis, Management, and Pathophysiology - Harsahaj Singh Wilkhoo; Harshavardhini Visvanathan; Swastika Chatterjee; Suhaib Hussain; Priyanshi Gundaniya; Vetrichelvan Francis; Bharat Singh; Ashwini Anil Pillai (International Journal of the Cardiovascular Academy, 2024)
Takotsubo syndrome (TTS), commonly referred to as stress-induced cardiomyopathy or broken heart syndrome, is a disorder characterized by acute left ventricular (LV) failure and apical ballooning that tends to occur due to extreme psychological or physical stress. Mainly affecting postmenopausal women, it has great similarities with other cardiac conditions like acute coronary syndrome. However, it has characteristic and distinct pathophysiology and disease progression. A wide range of diagnostic methods can be used, ranging from radiologic imaging to important biomarkers and biochemical analysis. These include cardiac magnetic resonance imaging, coronary angiography, echocardiography, echocardiogram, and inflammatory and cardiac biomarkers. There is a significant role for catecholamines in diagnosis. Key features include transient LV dysfunction and characteristic apical ballooning on imaging. The etiology involves a catecholamine surge leading to myocardial toxicity and microvascular dysfunction. Risk factors include age, sex, and stress, with additional associations such as pheochromocytoma and certain thyroid disorders. Management focuses on supportive care and pharmacological interventions, including beta-blockers, angiotensin converting enzyme inhibitors, and anticoagulants. Despite a good short-term prognosis, this condition can lead to severe complications and even sudden cardiac death. Long-term prognosis varies, with factors like reduced LV ejection fraction as well as old age affecting outcomes. This review summarizes the most updated information and is crucial for understanding TTS’s diagnostic and therapeutic strategies. This review underlines the pathophysiology, risk factors, management strategies, and importance of nutritional management. Future research is recommended for improving diagnostic and therapeutic strategies, emphasizing early and accurate detection to mitigate risks and enhance patient outcomes.